Racial Dichotomies in Employment Perceptions: An Empirical Study of Workers in Selected Atlanta-Based Firms - Jedel, Michael Jay; Kujawa, Duane (Academy of Management Journal, 1976)
A survey was conducted in five large firms during a study of barriers to minority employment. Black and white employee groups, similar in most characteristics, expressed perceptions of their treatment vis-à-vis one another in terms of hiring practices, compensation, promotion, and job satisfaction and treatment. Management implications of differing perceptions are discussed.